2020
DOI: 10.1007/s00464-020-07887-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Bariatric Surgery outcomes: the impact of preoperative elevated hemoglobin A1c levels on composite perioperative outcome measures

Abstract: Introduction The use of bariatric surgery in the management of obesity and its related morbidity has significantly increased in the US over the past decade. There is a lack of data on the impact of optimal preoperative glycemic control on the morbidity and mortality following bariatric surgery. The aim of this study was to analyze the impact of hemoglobin (Hb) A1c > 7 on outcomes among patients undergoing Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (SG). Methods Data were extracted from the Metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
6
0
3
Order By: Relevance
“…Additionally, we characterize patient demographics for those who may benefit from DJBL, including those with obesity and T2D. Considering substantial data supporting improved bariatric surgery outcomes following pre‐operative weight loss and improved glycemic control, 51–53 especially for those with severe obesity and metabolic complications, 52,54 it appears that DJBL may provide a potential optimization strategy. Further studies evaluating outcomes following DJBL prior to definitive bariatric surgery are required to evaluate this as a therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we characterize patient demographics for those who may benefit from DJBL, including those with obesity and T2D. Considering substantial data supporting improved bariatric surgery outcomes following pre‐operative weight loss and improved glycemic control, 51–53 especially for those with severe obesity and metabolic complications, 52,54 it appears that DJBL may provide a potential optimization strategy. Further studies evaluating outcomes following DJBL prior to definitive bariatric surgery are required to evaluate this as a therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conducted a multivariable logistic regression and reported that elevated HbA1c >7% was significantly associated with increased odds of having an adverse postoperative outcome following bariatric surgery. 12 Meister et al conducted a single-institution retrospective study to assess the clinical significance of peri-operative hyperglycemia on patients undergoing bariatric surgery and found perioperative hyperglycemia to be associated with higher composite infectious complications in patients with diabetes and non-diabetes. 14 On the other hand, Rawlins et al performed a single-institution retrospective analysis of 342 patients with T2DM undergoing bariatric surgery and found no difference in combined complication rates when comparing groups with HbA1c < 7% with HbA1c > 7%.…”
Section: Discussionmentioning
confidence: 99%
“…This, in our opinion, supports our findings on the stratification analysis, that the mild statistically significant increased risk demonstrated by the odds ratio is clinically insignificant. Hart et al 12 found that HbA1c >7% was associated with an increased risk of complications in the MBSAQIP database. 12 We hypothesize that the significant difference demonstrated by the authors in their study was due to the inclusion of patients without diabetes in their control group with HbA1c <7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations